PERAN SUPERVISI BK DALAM MENINGKATKAN PELAKSANAAN LAYANAN BIMBINGAN DAN KONSELING - Rahmawati, Novi; Wibowo, Agus; Pranoto, Hadi (Counseling Milenial (CM), 2023)
The aims of this reseach are: (1) to determine the role of supervision in planning counseling services at SMA Negeri 4 Metro. (2) to determine the role of supervision in BK supervision activities at SMA Negeri 4 Metro and (3) to determine the role of supervision of Guidance and Counseling in the evaluation of guidance and counseling services by guidance and counseling teachers at SMA Negeri 4 Metro.This research method uses qualitative research with descriptive research type. The presence of researchers as research data collectors as well as analyze data. The instrument in this study used interview sheets, observations, and documentation. Data analysis used inductive descriptive data analysis. The results of this study indicate that the role of guidance and counseling supervision in the planning aspect of guidance and counseling services to improve service quality is to examine, assess, and guide teachers in preparing service tools, questionnaires on student needs, helps provide input on how to identify student problems, examines programs guidance and provide eligibility for programs and RPL that have been made by the teacher. The role of guidance and counseling supervision in the implementation aspect of guidance and counseling services is to monitor, guide, and direct teachers in the implementation of services to comply with established assessment standards. The role of guidance and counseling supervision in the service evaluation aspect is to provide assistance to teachers in assessing and making service follow-up processes, providing suggestions and input to guidance and counseling teachers to always carry out evaluations immediately after carrying out service activities.